2019
DOI: 10.1097/sla.0000000000003301
|View full text |Cite
|
Sign up to set email alerts
|

Surgery Improves Survival After Neoadjuvant Therapy for Borderline and Locally Advanced Pancreatic Cancer

Abstract: Objective: Neoadjuvant therapy (NAT) has become part of the multimodality treatment for borderline resectable pancreatic cancer (BRPC) and locally advanced pancreatic cancer (LAPC). Summary Background Data: It is currently uncertain which are the preferable NAT regimens, who benefits from surgery, and whether more aggressive surgical strategy is motivated. Methods: A retrospective cohort analysis was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
118
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 41 publications
7
118
1
Order By: Relevance
“…Favorable outcomes in patients who achieved CA 19-9 response and conversion surgery were in line with the results of prior studies. 26 , 28 , 29 Tumor response and CA 19-9 response to FOLFIRINOX may be reliable interim indicators for survival outcomes. In contrast to our findings, tumor response was not associated with OS in a previous study including 194 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Favorable outcomes in patients who achieved CA 19-9 response and conversion surgery were in line with the results of prior studies. 26 , 28 , 29 Tumor response and CA 19-9 response to FOLFIRINOX may be reliable interim indicators for survival outcomes. In contrast to our findings, tumor response was not associated with OS in a previous study including 194 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralization of IFN-γor adoptive transfer of Tregs significantly reduced increased mortality (Grayson et al, 2018). In another study using murine models of influenza virus and respiratory syncytial virus (Rangelova et al, 2019), significantly altered gut microbiota diversity, with a decrease in Firmicutes phyla abundance and an increase in Bacteroidetes was observed in mice infected with influenza virus or RSV. Viral lung infections also caused an increase in colonic Muc5ac levels and fecal lipocalin-2, indicating low-grade inflammation in gut (Groves et al, 2018).…”
Section: Viral and Fungal Infectionsmentioning
confidence: 96%
“…Many retrospective studies have shown that among patients with locally advanced, unresectable PDAC undergoing successful conversion chemotherapy and surgical exploration, those who received resection had a substantial survival benefit as compared with non-resectable patients [44][45][46]. Patient selection in these studies was based on disease control achieved with conversion therapy, whereas resectability was assessed by exploration.…”
Section: Surgerymentioning
confidence: 99%